Associations of night sleep duration and daytime napping with diabetic retinopathy in patients with type 2 diabetes - Lei Xi; Xiaohui Sun; Zhimin Feng; Yanan Cao (Frontiers in Endocrinology)
AimsThe purpose of this study was to evaluate the relationship between night sleep duration, daytime napping, and diabetic retinopathy (DR) in type 2 diabetes (T2D) patients and to explore the potential mediating role of metabolic factors.MethodsIn this cross-sectional, retrospective study, night sleep and napping were assessed according to the standardized questionnaire. The metabolic factors in the examination were systolic blood pressure (SBP), diastolic blood pressure (DBP), body mass index (BMI), and HbA1c. Multivariate logistic regression and stratified and conjoint analysis were carried out. In addition, causal mediation analysis was performed to explore the mediating role.ResultsA total of 2,433 patients [mean (SD) age, 55.82 (11.66) years; 40.07% women] were included in the final analysis. The prevalence of DR was 15.95%. Compared with reference groups, patients with long sleep [odds ratio (OR), 1.31, 95% confidence interval (CI), 1.01–1.70] and long nap (1.09, 1.04–1.23) were both associated with DR, and stratified analysis showed that this association varied among different sex and diabetes duration groups. Conjoint analysis showed that patients with both long sleep and long naps had a significantly increased risk of DR (1.75, 1.13–2.71). Mediation analysis showed that metabolic factors partially mediated this association between night sleep, naps, and DR, contributing to 9.8% and 16.3% of the total effects, respectively.ConclusionsLong sleep and long nap were associated with DR, and male patients with T2D with a shorter course (<5 years) especially need to be vigilant. The effects of night sleep and naps on DR could be superimposed, and metabolic factors partially explain the underlying mechanism.